Total Defense Systems in National Resilience Strategy: Assessing Indonesia’s Readiness to Confront Hybrid Threats - Robbi Adhilni; Rudy Agus Gemilang Gultom; Herlina Juni Risma Saragih; Angga Aria Kusuma (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
In an increasingly complex multidimensional threat environment, defense strategies can no longer rely solely on military approaches. This study aims to assess Indonesia’s readiness in implementing the Total Defense System (TDS) to address hybrid threats such as cyberattacks, disinformation, climate change, economic crises, and global pandemics. Using a comparative literature review approach, this study draws from Scopus-indexed scientific publications and relevant national policy documents, focusing on lessons from countries like Singapore, Finland, Sweden, and Switzerland. The findings reveal several major challenges, including weak inter-sectoral coordination, limited cyber defense infrastructure, and low civilian participation in national preparedness. Nonetheless, strategic opportunities exist through military modernization, enhanced digital institutional capacity, and increased civil involvement. This study recommends strengthening digital literacy, reforming cybersecurity regulations, and promoting economic resilience as key components of an adaptive and sustainable TDS policy integration